Egy hallgatás története – gyerekirodalom: (Oravecz Imre: Máshogy mindenki más, 1979, 1996, 2018) - Pataki, Viktor (Studia Litteraria, 2019)
The study attempts to expound the history of reception of Imre Oravecz’s book Máshogy mindenki más (Everyone Is Different in a Different Way). Oravecz published his third book (the first edition) in 1979. From a historical and explicitly YA perspective it was treated as a silent achievement, because this volume has almost disappeared among the other books of the author. However, this is not only important in the context of the author’s oeuvre, but also in the Hungarian children’s literature research. This study tries to examine the central role of this book with regard to possibilities and problems of the current YA studies. In the context of the rhetorical reading crucial questions may arise, such as the role of canon, the correlation between reading and game.